Structural Equation Modeling Method to Analyze the Influence of Learning Style, Mathematics Resilience, and Learning Motivation on Mathematical Problem-Solving Ability - Edo Dwi Cahyo; Juitaning Mustika; Dwi Retno Puspita Sari; Fertilia Ikashaum; Ika Yuni Wulansari (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractThis study aimed to analyze the influence of learning styles, mathematics resilience, and learning motivation on elementary school students’ mathematical problem-solving abilities. The research involved 131 students from three elementary schools in Metro and East Lampung, Indonesia and employed Structural Equation Modeling (SEM) for data analysis. The results showed that all three variables significantly affected students' mathematical problem-solving abilities. Learning motivation had the strongest influence (C.R = 1.880, p = 0.034), followed by mathematics resilience (C.R = 1.754, p = 0.045) and learning style (C.R = 1.729, p = 0.040). The three variables collectively contributed 78.3% to the variance in students' mathematical problem-solving abilities, indicating a strong overall effect. These findings suggest that enhancing students’ learning motivation, building mathematical resilience, and aligning teaching methods with students’ learning styles are effective strategies to improve their mathematical problem-solving performance. The study recommends the implementation of adaptive and inclusive teaching approaches that consider cognitive and psychological factors in elementary mathematics education.Keywords: SEM method, learning style, mathematics resilience, learning motivation, problem-solving ability. AbstrakPenelitian ini bertujuan untuk menganalisis pengaruh gaya belajar, ketahanan matematika, dan motivasi belajar terhadap kemampuan pemecahan masalah matematika siswa sekolah dasar. Penelitian ini melibatkan 131 siswa dari tiga sekolah dasar di Metro dan Lampung Timur, Indonesia dan menggunakan Structural Equation Modeling (SEM) untuk analisis data. Hasil penelitian menunjukkan bahwa ketiga variabel tersebut secara signifikan memengaruhi kemampuan pemecahan masalah matematika siswa. Motivasi belajar memiliki pengaruh paling kuat (C.R = 1,880, p = 0,034), diikuti oleh ketahanan matematika (C.R = 1,754, p = 0,045) dan gaya belajar (C.R = 1,729, p = 0,040). Ketiga variabel tersebut secara kolektif memberikan kontribusi sebesar 78,3% terhadap varians kemampuan pemecahan masalah matematika siswa, yang menunjukkan efek keseluruhan yang kuat. Temuan ini menunjukkan bahwa peningkatan motivasi belajar siswa, membangun ketahanan matematika, dan menyelaraskan metode pengajaran dengan gaya belajar siswa merupakan strategi yang efektif untuk meningkatkan kinerja pemecahan masalah matematika mereka. Penelitian ini merekomendasikan penerapan pendekatan pengajaran yang adaptif dan inklusif yang mempertimbangkan faktor kognitif dan psikologis dalam pembelajaran matematika di sekolah dasar.Kata kunci: metode SEM, gaya belajar, ketahanan matematika, motivasi belajar, kemampuan memecahkan masalah.